2016
DOI: 10.18290/rpsych.2016.19.1-1en
|View full text |Cite
|
Sign up to set email alerts
|

When the need for closure promotes complex cognition

Abstract: Lay epistemic theory is one of the most popular theoretical frameworks describing the knowledge formation process. According to it, the central variable determining the epistemic process is the need for cognitive closure. In most cases, high levels of this motivation are associated with simplified and accelerated processing of information. This can lead to an overly simplified understanding of this variable. In fact, there are reasons to believe that the typical relationship is reversed under certain circumsta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…High NFC group members may have been more sensitive to epistemic authorities for their enhanced inclination towards simplistic heuristics. Nevertheless, because source expertise constitutes relevant (albeit indirect) evidence of the quality of those ideas, high NFC group members in our study may have also demonstrated to be more “forward-thinking” than low NFC group members (Strojny et al, 2016).…”
Section: Discussionmentioning
confidence: 75%
“…High NFC group members may have been more sensitive to epistemic authorities for their enhanced inclination towards simplistic heuristics. Nevertheless, because source expertise constitutes relevant (albeit indirect) evidence of the quality of those ideas, high NFC group members in our study may have also demonstrated to be more “forward-thinking” than low NFC group members (Strojny et al, 2016).…”
Section: Discussionmentioning
confidence: 75%
“…Information that is inconsistent with the individual's system of knowledge is mostly ignored. Hence, it is difficult for such persons to change their opinions, convictions and beliefs under the influence of incoming information [36,41].…”
Section: Introductionmentioning
confidence: 99%
“…Even though recent findings sustain that NFCC—under conditions where lengthier and more effortful means are instrumental to attain closure—may actuate more systematic cognitive processing ( Jaśko et al, 2015 ; Roets et al, 2015 ; Kossowska et al, 2016 ; Strojny et al, 2016 ; Szumowska and Kossowska, 2017 ), in general, previous research has shown that NFCC more often leads to less effortful, faster, and more superficial information processing (e.g., they base judgments on early appearing information, preexisting attitudes, and stereotypes; see Kruglanski and Webster, 1996 ; for overview). The above findings indicate that high-NFCC individuals strive for simplification, order, and predictability in order to reduce uncertainty and reach epistemic clarity.…”
Section: Introductionmentioning
confidence: 99%